Clinical result of structural augmentation with cannulated bone screws for the treatment of osteonecrosis of the femoral head - Yang, Shu‐hua (Orthop Surg, 2009)
Objective:  To evaluate the results of treatment of osteonecrosis of the femoral head by structural augmentation through a routine core decompression procedure combined with insertion of cannulated bone screws incorporating autogenous bone graft and biomaterial containing decalcified bone matrix. Methods:  From February 2002 to February 2005, 31 patients (33 hips) with femoral head necrosis were treated in our hospital using insertion of cannulated bone screws incorporating autogenous bone graft. There were 18 men and 13 women with an average age of 37 years (range, 27–49). The Steinberg classification was stage I for 20 hips (61%) and stage II for 13 hips (39%). Clinical and radiographic evaluations were performed on all patients. The patient's satisfaction was also assessed. Results:  All 31 patients (33 hips) were retrospectively studied after a mean follow‐up of 38 months (range, 18–48). The average Harris hip score was 76 before surgery and 91 at the final follow‐up. All patients stated that they were satisfied and had significantly reduced pain. According to the Harris hip score system, 21 cases were excellent, 8 good and 2 fair. No complications, such as wound infection, subtrochanteric fracture, neuropathy and deep vein thrombosis, were found. Conclusion:  Structural augmentation using the insertion of cannulated bone screws incorporating autogenous bone graft is an effective option for Steinberg I–II stages of femoral head necrosis. Further study is needed to confirm mid‐ and long‐term results.